Development of a short and effective shoulder external rotation strength program in handball: A delphi study. (July 2020) - Fredriksen, Hilde; Cools, Ann; Myklebust, Grethe
Abstract: Background: Weakness of the shoulder external rotators (ER) is one of the main risk factors for shoulder pain in handball. Short, effective shoulder ER strength programs the players will adhere to are lacking. Objectives: to develop a short and effective shoulder ER strength program, handball players will adhere to. Methods: We conducted a modified Delphi study, including experts in the field of shoulder, strength training and handball. In the first round, the experts were asked to rate eight pre-defined shoulder ER exercises on efficacy and adherence and to suggest other preferred exercises. In round two, they were asked to rate the new exercises from round one. In round three, they received a statistical summary of the panels scores, their own score and a summary of the suggestions. Based on the feedback, the experts were asked to revise their response. Results: Sixteen experts completed three rounds with 100% response rate. Twenty-eight exercises were rated. We reached consensus for both efficacy and adherence for two exercises, ER in 90° abduction in a bent-over squat position and ER in 90° abduction combined with horizontal abduction and trunk rotation in a push-up position. Conclusion: We reached consensus for both efficacy and adherence for two exercises. Highlights: Two shoulder external rotation exercises reached efficacy and adherence consensus. These results may assist the clinician or coach in selecting effective exercises. The efficacy of the program will be tested out in a randomized controlled study.